2013
DOI: 10.1177/1087724x12469795
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Mobility Management in the United States

Abstract: Mobility management aims at the provision of accessible, multimodal, and affordable transportation services to all individuals in a community, including the elderly, disabled and lower income individuals. It has much potential to deliver public transit services in a cost efficient way and uses a customer driven and market based approach to make it more responsive to the needs of individuals in a community. In mobility management, there is much emphasis on coordination and collaboration, which makes mobility ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Majumdar et al emphasised role of coordination and collaboration for mobility management in the USA. The study observes existence of several rules and regulations aimed at mobility management besides the national advocacy groups promoting the cause and concludes that sharing of information and communication across the stakeholders is essential for successfully ensuring transport for all [15].…”
Section: Research Surveymentioning
confidence: 99%
“…Majumdar et al emphasised role of coordination and collaboration for mobility management in the USA. The study observes existence of several rules and regulations aimed at mobility management besides the national advocacy groups promoting the cause and concludes that sharing of information and communication across the stakeholders is essential for successfully ensuring transport for all [15].…”
Section: Research Surveymentioning
confidence: 99%
“…Past research has shown mobility increases the quality of life and livability of a region (Burns, 1999;Ripplinger et al, 2012), the elderly need improved transportation options (Choi et al, 2012;Glasgow & Blakely, 2000), and the demand for mobility is increasing (Coughlin & D'Ambrosio, 2012;Shaheen, 2012). Studies also find regions are designing and implementing innovative approaches to meet mobility needs (Cobb & Coughlin, 2004;Mujumdar et al, 2013;Shaheen, 2012). Gwilliam (2008) reviews the international literature on transit economics, albeit with a focus on urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Une définition simple de la GDT est proposée par Berman et Radow (1997) (Majumdar et al, 2012). La mise en oeuvre de la GDT implique ainsi une bonne part d'activités de promotion des changements de comportement, bien qu'elle n'en reste pas là; elle implique aussi des programmes concrets et des infrastructures physiques pour appuyer ces changements (Lim, 1997).…”
Section: Définition Et Objectifs De La Gdtunclassified